Use of antibiotics and risk of type 2 diabetes, overweight and obesity: the Cardiovascular Risk in Young Finns Study and the national FINRISK study - Nuotio Joel; Niiranen Teemu; Laitinen Tomi T.; Miller Jessica; Sabin Matthew A.; Havulinna Aki S.; Viikari Jorma S. A.; Rönnemaa Tapani; Hutri-Kähönen Nina; Laitinen Tomi P.; Tossavainen Päivi; Salomaa Veikko; et al. (Springer Nature, 2025)
Purpose: To investigate whether exposure to systemic antibiotics influences the risk of developing type 2 diabetes and overweight/obesity.
Methods: The study sample comprised 2209 (110 with incident diabetes) participants from the population-based Cardiovascular Risk in Young Finns Study (YFS) aged 24-39 years in 2001. The exposure was national linked register data on purchased antibiotic courses between 1993 and 2001. Clinical examinations including BMI were conducted in 2001, 2007 and 2011. Participants with prevalent diabetes in 2001 were excluded. Data on type 2 diabetes was also obtained from two national registers until 2017. Data from four population-based National FINRISK studies were used for replication (N = 24,674, 1866 with incident diabetes).
Results: Prior antibiotic exposure (> 5 versus 0-1 antibiotic courses) was associated with subsequent type 2 diabetes in both YFS (OR 2.29; 95%CI 1.33-3.96) and FINRISK (HR 1.73; 95%CI 1.51-1.99). An increased risk for type 2 diabetes was observed in YFS (OR 1.043; 95%CI 1.013-1.074) and FINRISK (HR 1.022; 95%CI 1.016-1.029) per course. Exposure to antibiotics increased the risk of overweight/obesity (BMI > 25 kg/m2) after a 10-year follow-up in YFS (OR 1.043; 95%CI 1.019-1.068) and in FINRISK (OR 1.023; 95%CI 1.018-1.029) at baseline per antibiotic course. Adjustments for confounders from early life in YFS and at baseline in FINRISK, including BMI, socioeconomic status, smoking, insulin, blood pressure, and physical activity, did not appreciably alter the findings.
Conclusion: Our results show that exposure to antibiotics was associated with increased risk for future type 2 diabetes and overweight/obesity and support judicious antibiotic prescribing.